Bimbingan dan Konseling Karir Remaja “Studi Komparasi SMP IT Abu Bakar dan SMP Taman Dewasa Ibu Pawiatan Yogyakarta” - Ardiansyah, Ardiansyah (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2018)
The implementation of counseling career counseling of students in SMK IT Abu Bakar Yogyakarta and SMP Taman Dewasa Ibu Pawiatan Yogyakarta in career development towards students shows the difference both in terms of service program of career counseling counseling, or career service orientation toward students. This we can see BK care program services in SMK IT Abu Bakar we are good enough value for the development of students starting with the measurement of talent interest SMP IT Abu Bakar using AMT test equipment in measuring interest in student talent. The guidance of career counseling of SMP IT Abu Bakar is divided into classes for 7th and 8th grade leading to some extracurricular activities and study club, and for the 9th grade more towards organizing and knowing the next level school that is in high school and various majors in SMA, or even SMK. And as for the career guidance program at SMP Taman Dewasa Ibu pawiatan is BK Career program at SMP Taman Dewasa Ibu Pawiyatan Yogyakarta including daily service program, weekly service, and monthly service. While Pelakasanaan BK Kariri in SMP Taman Marga Pawiyatan more emphasis on cultural and social extra kulikuler development activities and to support the preparation of career class 9, SMP park adult Ms. Pawiyatan career mapping and counseling or the introduction of some secondary or high school level. The concept of BK career in SMP Taman Marga Pawiyatan adult is easier and flexible to solve the problem of the students. The guidance of career counseling submitted by the author in this journal must be a scholarly contribution of academic people in reviewing about the implementation of career counseling guidance in applied in school in order to develop student's career